2002
DOI: 10.1300/j076v34n03_04
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Retention in a Therapeutic Community for Incarcerated Substance Abusers

Abstract: In this paper, factors associated with retention in CREST, a therapeutic community for incarcerated substance abusers, are explored. Few studies have simultaneously examined different types of potential predictors that research has identified as important for retention. We do so here in an effort to clarify factors associated with retention. Retention is measured both in terms of program completion and days in treatment. The results indicate that only one predictor-frequent marijuana use prior to incarceration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
1
17
1
2
Order By: Relevance
“…Con respecto al tiempo de estancia, se encuentra que la tasa de retención del programa a los tres meses fue moderadamente más elevada que la encontrada en otros trabajos (68.3%), que oscila en torno al 50% (Condelli y Dunteman, 1993;De Leon y Schwartz, 1984;Gossop, Marsen, Stewart y Rolfe, 1999;Maglione, Chao y Anglin, 2000;Mulder et al, 2009;Nielsen y Scarpitti, 2002). De acuerdo con otros autores (Condelli y De Leon, 1993;Condelli, 1994;De Leon, 1991), se observa que para que un paciente llegue a presentar mejoría, se requiere al menos tres meses de estancia en CT, pues tan sólo un 28% de los pacientes alcanzan cambios clínicamente relevantes antes de los 90 días.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Con respecto al tiempo de estancia, se encuentra que la tasa de retención del programa a los tres meses fue moderadamente más elevada que la encontrada en otros trabajos (68.3%), que oscila en torno al 50% (Condelli y Dunteman, 1993;De Leon y Schwartz, 1984;Gossop, Marsen, Stewart y Rolfe, 1999;Maglione, Chao y Anglin, 2000;Mulder et al, 2009;Nielsen y Scarpitti, 2002). De acuerdo con otros autores (Condelli y De Leon, 1993;Condelli, 1994;De Leon, 1991), se observa que para que un paciente llegue a presentar mejoría, se requiere al menos tres meses de estancia en CT, pues tan sólo un 28% de los pacientes alcanzan cambios clínicamente relevantes antes de los 90 días.…”
Section: Discussionunclassified
“…Los resultados de este estudio han apoyado esta hipótesis, constatándose que la existencia de comorbilidad psicopatológica estuvo asociada a un abandono precoz de CT. Es decir, los pacientes con otros trastornos mentales, además de los relacionados con el consumo de sustancias, permanecen en el recurso menos días, obtienen un menor porcentaje de altas terapéuticas y cambios clínicos menos relevantes. Este hallazgo ha sido también informado por otros autores (Agostini et al, 1991;Broome et al, 1999;Condelli, 1994;Dekel, Benbenishty y Amram, 2004;Levin, Evans, Vosburg, Horton, Brooks y Ng, 2004;Mulder et al, 2009;Nielsen y Scarpitti, 2002;Van Stelle, Blumer y Moberg, 2004).…”
Section: Discussionunclassified
“…Therefore, it is unclear if these findings would extend to females and individuals of other ethnicities and socioeconomic status. Finally, we did not conduct a comprehensive assessment of legal and criminal history, which evidence indicates may affect treatment retention (Nielson & Scarpitti, 2002), highlighting the importance of including this variable in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, although individuals in the legal system may have greater external pressure for change than those voluntarily entering treatment, this pressure may or may not translate to greater treatment gains (De Leon, 1996). The evidence surrounding the role of a more internalized motivation for change as a factor influencing the outcome of mandated treatments is also mixed, with some studies suggesting that stronger motivation to change leads to greater compliance and retention in treatment (Knight, Hiller, Broome, & Simpson, 2000;Sung, Belenko, Feng, & Tabachnick, 2004) whereas other research groups have found a null relationship (Kelly, Finney, & Moos, 2005;Nielsen, & Scarpitti, 2002;Hopwood, Baker, & Morey, 2008a, 2008b.…”
mentioning
confidence: 99%